Functional outcome of Dynamic Hip Screw versus Proximal Femoral Nail in treatment of intertrochanteric fracture of the femur - Basnyat, Sagun; Lakhey, Shishir; Khanal, Krishna Raj (Purbanchal University Health Journal, 2025)
Introduction: Internal fixation is the most appropriate treatment for intertrochanteric fractures. The mainstay treatment of intertrochanteric fracture is fixation with either an extramedullary weight bearing device like DHS (Dynamic Hip Screw) or an intramedullary weight sharing device like PFN (Proximal Femoral Nail). The functional superiority of intramedullary devices over extramedullary devices has already been established. We carried out this study to evaluate the functional outcome of these implants in stable intertrochanteric fractures. Objective: The objective of the study was to evaluate the functional outcome of Proximal Femoral nail versus Dynamic Hip Screw fixation in Intertrochanteric fracture in Nepalese population aged 50 years and above. Method: A prospective comparative cross-sectional hospital based study was conducted on 30 patients admitted with intertrochanteric fracture, who were allocated alternatively with DHS or PFN surgery and were followed up for 1 year. The intertrochanteric fractures of Boyd and Griffin type II and III were included in study. The parameters studied were the demographic profile, type and mechanism of injury, tip apex distance, duration of hospital stay, time of union and functional outcome as measured by Harris Hip Score and Palmer and Parker Mobility Score . Result: The study did not find a statistically significant difference in the functional outcome between these two methods of treatments as measured by Harris Hip Score. However, there was a better functional outcome among the age group 81years and above when operated by PFN. Conclusion: Patients with Boyd and Griffin type 2 and 3 intertrochanteric fractures will have almost the same mobility score after surgical fixation via either DHS or PFN. However, PFN has better functional outcomes among those aged 81 years and above. These patients will have almost the same mobility score after surgical fixation by either DHS or PFN.